Chryzostomowa terminologia wychowania - Osek, Ewa (Vox Patrum, 2009)
This paper is the study of the Greek terms using by John Chrysostom on rearing, upbringing, training and teaching of children. The analyse of these terms and their use in all the John Chrysostom's writings shows as strong influence of the Atttic writers' vocabulary (especiallty Platoʼs), even in his commentaries on the Scriptural verses, as of the early Christian literature (New Testament, Clement of Alexandria, Gregory of Nyssa).